KARAKTER MORFOLOGI DAN ANATOMI PISANG DIPLOID DAN TRIPLOID - Ari Sunandar; Adi Pasah Kahar (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Indonesia is the center of origin of bananas, and also the center of diversity with approximately more than 325 banana cultivars were found in Indonesia. The anatomical feature is essential as a basis for classification as well as the morphological feature. This research aimed to describe the morphological and anatomical characteristics of diploid Musa balbisiana and triploid Musa paradisiaca 'Kepok' bananas. Morphological characterizations were conducted according to the IPGRI descriptors for bananas (Musa spp.). Musa paradisiaca 'Kepok' was collected from Pontianak West Kalimantan and Musa balbisiana was collected from Nipah Panjang village Kubu Raya district West Kalimantan. The root, petiole, and leaf were dissected from banana samples for anatomical preparation. The microscope slide was prepared using paraffin method, stained with 1% safranine and 1% alcian blue. The anatomical characteristics of root and petiole of diploid Musa balbisiana and triploid Musa paradisiaca 'Kepok' were considerably similar. The difference between diploid and triploid banana leaf anatomy was the number of hypodermal layers. These sort of anatomical characterization could be applied as a reference for banana cultivars breeding.